The Rave diet & lifestyle - Anderson, Michael ([United States] : www.RaveDiet.com, 2009)
Explains why the U.S. government guidelines for nutrition are anything but healthy. Links the eating of an animal-based diet with heart disease, cancer, diabetes and other serious health problems. Introduces the RAVE diet, which consists of no refined foods, no animal foods, no vegetable oils, no exceptions & exercise. Also discusses the devastating effects on the environment of a meat-eating nation.
Introduction: The tortoise and the hart -- Diet, disease & weight loss -- The RAVE diet & lifestyle -- Notes -- RAVE diet guidelines -- Sample recipes.
"The natural foods diet with meals that heal"--Cover
Includes bibliographical references and index.
Keywords: Cooking (Natural foods); Natural foods; Food habits; Reducing diets -- Recipes; Health; Nutrition; Nutrition policy -- United States; Nutritionally induced diseases -- United States; Diet -- United States; Diet -- Environmental aspects